Post‐prandial reflux suppression by a raft‐forming alginate (Gaviscon Advance) compared to a simple antacid documented by magnetic resonance imaging and pH‐impedance monitoring: mechanistic assessment in healthy volunteers and randomised, controlled, double‐blind study in reflux patients. Issue 11 (18th April 2013) - Sweis, R.; Kaufman, E.; Anggiansah, A.; Wong, T.; Dettmar, P.; Fried, M.; Schwizer, W.; Avvari, R. K.; Pal, A.; Fox, M.
Summary Background Alginates form a raft above the gastric contents, which may suppress gastro‐oesophageal reflux; however, inconsistent effects have been reported in mechanistic and clinical studies. Aims To visualise reflux suppression by an alginate–antacid [Gaviscon Advance (GA), Reckitt Benckiser, UK] compared with a nonraft‐forming antacid using magnetic resonance imaging (MRI), and to determine the feasibility of pH‐impedance monitoring for assessment of reflux suppression by alginates. Methods Two studies were performed: (i) GA and antacid (Alucol, Wander Ltd, Switzerland) were visualised in the stomach after ingestion in 12 healthy volunteers over 30 min after a meal by MRI, with reflux events documented by manometry. (ii) A randomised controlled, double‐blind cross‐over trial of post‐prandial reflux suppression documented by pH‐impedance in 20 patients randomised to GA or antacid (Milk of Magnesia; Boots, UK) after two meals taken 24 h apart. Results MRI visualized a "mass" of GA form at the oesophago‐gastric junction (OGJ); simple antacid sank to the distal stomach. The number of post‐prandial common cavity reflux events was less with GA than antacid [median 2 (0–5) vs. 5 (1–11); P < 0.035]. Distal reflux events and acid exposure measured by pH‐impedance were similar after GA and antacid. There was a trend to reduced proximal reflux events with GA compared with antacid [10.5 (8.9) vs. 13.9 (8.3); P = 0.070]. Conclusions Gaviscon Advance forms a 'mass' close to the OGJ and significantly suppresses reflux compared with a nonraft‐forming antacid. Standard pH‐impedance monitoring is suitable for clinical studies of GA in gastro‐oesophageal reflux disease patients where proximal reflux is the primary outcome.